2021
DOI: 10.3390/md19110638
|View full text |Cite
|
Sign up to set email alerts
|

From Natural Xanthones to Synthetic C-1 Aminated 3,4-Dioxygenated Xanthones as Optimized Antifouling Agents

Abstract: Biofouling, which occurs when certain marine species attach and accumulate in artificial submerged structures, represents a serious economic and environmental issue worldwide. The discovery of new non-toxic and eco-friendly antifouling systems to control or prevent biofouling is, therefore, a practical and urgent need. In this work, the antifouling activity of a series of 24 xanthones, with chemical similarities to natural products, was exploited. Nine (1, 2, 4, 6, 8, 16, 19, 21, and 23) of the tested xanthone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Xanthones 2 – 11 , 13 – 37 , 39 , and 40 ( Table 1 ) were previously synthesized in our laboratory in the scope of other projects via three traditional methods ( Scheme 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]: condensation of salicylic acid or salicylic ester with a phenol derivative (a), via benzophenone (b), or via diphenyl ether intermediates (c).…”
Section: Resultsmentioning
confidence: 99%
“…Xanthones 2 – 11 , 13 – 37 , 39 , and 40 ( Table 1 ) were previously synthesized in our laboratory in the scope of other projects via three traditional methods ( Scheme 1 ) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]: condensation of salicylic acid or salicylic ester with a phenol derivative (a), via benzophenone (b), or via diphenyl ether intermediates (c).…”
Section: Resultsmentioning
confidence: 99%
“…This napyradiomycins displayed settlement results of M. galloprovincialis larvae with an EC 50 of less than 5 μg/mL and a LC 50 /EC 50 ratio greater than 15 (Pereira et al, 2020). Further, the EC 50 of (2) was lower than that of other synthesized compounds or compounds from distinct bioresources (Neves et al, 2021;Pereira et al, 2021;Resende et al, 2021).…”
Section: Assessment Of Antifouling Properties On Mytilus Galloprovinc...mentioning
confidence: 89%
“…The secondary metabolite xanthone derivatives, which are widely present in marine and terrestrial plants and animals, have been shown to have antifouling activity yet are still not used for marine antifouling. Resende et al [ 47 ] explored the antifouling activity of a series of 24 synthetic xanthone analogs for the first time to further explore the potential of xanthone derivatives for antifouling. The test results showed that xanthones 21 and 23 (the chemical molecular structure is shown in Figure 8 ) were the most effective in inhibiting larval sedimentation (EC 50 of 7.28 and 3.57 µM, respectively), and, with a therapeutic ratio (LC 50 /EC 50 ) > 15 for xanthone 23, this synthetic analog has great potential for marine antifouling applications.…”
Section: New Environmentally Friendly Antifouling Coatingmentioning
confidence: 99%